2021
DOI: 10.3389/fphar.2020.587445
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: IL-21 and Bcl-6 Regulate the Proliferation and Secretion of Tfh and Tfr Cells in the Intestinal Germinal Center of Patients With Inflammatory Bowel Disease

Abstract: Objective: This study aimed to investigate the effect of interleukin (IL)-21 and B cell lymphoma protein-6 on germinal center follicular helper T (Tfh) cells and follicular regulatory T (Tfr) cells and its relationship with the clinical features of inflammatory bowel disease (IBD).Methods: The expression of peripheral blood cytokines IL-21 and Bcl-6 mRNA was detected by reverse transcription–polymerase chain reaction. The distribution characteristics of Tfh and Tfr cells were detected using the triple immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The value of Mayo clinic score, erythrocyte sedimentation rate (ESR), or C-reactive protein (CRP) in UC patients was positively correlated with frequency of circulating Tfh cells [ 64 ]. Bcl-6 mRNA and Tfh cells in the germinal center were increased in the UC groups compared with that in the control group [ 65 ]. Recent studies further showed that Tfh cells were significantly increased in active UC patients compared with stable remission UC patients and healthy controls.…”
Section: The Role Of Tfh Cells and Il-21 In Ibdmentioning
confidence: 99%
See 4 more Smart Citations
“…The value of Mayo clinic score, erythrocyte sedimentation rate (ESR), or C-reactive protein (CRP) in UC patients was positively correlated with frequency of circulating Tfh cells [ 64 ]. Bcl-6 mRNA and Tfh cells in the germinal center were increased in the UC groups compared with that in the control group [ 65 ]. Recent studies further showed that Tfh cells were significantly increased in active UC patients compared with stable remission UC patients and healthy controls.…”
Section: The Role Of Tfh Cells and Il-21 In Ibdmentioning
confidence: 99%
“…The value of the Mayo clinic score, erythrocyte sedimentation rate (ESR), or C-reactive protein (CRP) in UC patients was negatively correlated with circulating Tfr cells and Tfr/Tfh ratio [ 64 ]. The number of Tfr cells was also reduced in the intestinal germinal center of the UC groups compared with that of the control group [ 65 ]. Recent studies further showed that circulating Tfr was decreased in active UC patients compared with stable remission UC patients and healthy controls and Tfr was negatively correlated with serum IgG, circulating new memory B cells, plasmablasts, and clinical characteristics [ 66 ].…”
Section: The Role Of Tfh Cells and Il-21 In Ibdmentioning
confidence: 99%
See 3 more Smart Citations